The Effect of Organizational Culture, Job Satisfaction on Entrepreneurship and Innovativeness in SMEs in Bogor City - Hidayati, Nanda; Notosudjono, Didik; Sunaryo, Widodo (The Es Economics and Entrepreneurship, 2023)
This study looks into the connections between innovation, entrepreneurship, work happiness, and organizational culture in Small and Medium-Sized Enterprises (SMEs) located in Bogor City. This study looks at the link between these factors utilizing a quantitative method in which SPSS is used. The results validate the hypotheses (H1 and H2) by demonstrating the strong influence of corporate culture on entrepreneurship and innovativeness. Furthermore, entrepreneurship and innovativeness are significantly positively impacted by job satisfaction, supporting hypotheses (H3 and H4). Moreover, H5 was supported by the finding that entrepreneurship was a major predictor of innovativeness. These results highlight the critical roles that job happiness and company culture play in encouraging entrepreneurial endeavors, which in turn boost SMEs' capacity for innovation. The study's conclusions offer useful advice to Bogor City's small business owners and managers, offering methods for enhancing worker happiness, creating a supportive workplace culture, and eventually encouraging innovation in SMEs.